Atypical Clinical Presentation of Hidradenitis Suppurativa in a Patient with Severe Mannose-Binding Lectin Deficiency - Shashank Bhargava; Nils Becker; George Kroumpouzos (Karger Publishers, 2020)
Mannose-binding lectin (MBL) deficiency is associated with recurrent infections, autoimmune and inflammatory skin disease, and vascular complications. MBL deficiency is not a recognized comorbidity in hidradenitis suppurativa (HS); the latter is associated with the group of autoinflammatory disorders. A 32-year-old woman presented with a history of recurrent painful, deep-seated abscesses and pustular lesions since the age of 13 years. Lesions were noted predominantly in HS distribution, i.e., submammary, inguinal, and perianal areas were affected. However, unusual locations (jawlines, neck) were also affected. The patient fulfilled the clinical criteria for HS but the presentation was atypical because lesions were noted in unusual locations, most lesions were in Hurley stage 1 (sparsity of sinus tracts and scarring), and most cultures from abscesses and pustular lesions were negative. The excruciating pain caused by constantly developing abscesses had a profound impact on the patient's quality of life. Laboratory workup showed an exceptionally low serum MBL level. Treatment was challenging with only a temporary, mild response to oral antibiotic therapy and no response to immunosuppressive and hormonal therapies. This atypical HS presentation may reflect an enhancement of proinflammatory mechanisms. Health care providers should be aware of this clinicopathologic presentation so that the establishment of HS diagnosis is not delayed and the patient receives appropriate counseling.